On a representation of smooth invariants of Coxeter groups in terms of anisotropic spaces - Gokhman, A. O. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
A smooth function invariant under the action of the Coxeter group can be represented as a function of basic invariants. We propose to describe the latter in terms of special anisotropic spaces, which enables us to obtain more precise estimates of its smoothness.